The Obstacles in Implementing the Independent Curriculum in Mathematics Learning: A Review from the Perspective of Social Constructivism Philosophy and Progressive Educators - Mariani Manik, Mariani Manik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This article aims to review the various challenges that arise in implementing the Independent Curriculum in mathematics learning, and view it from the perspective of the philosophy of Mathematics Education. This study is based on an analysis of related literature to identify the main obstacles faced by teachers and students, such as limited resources, readiness of teaching staff, and resistance to changing methods. In addition, this article highlights how principles in educational philosophy, such as constructivism and progressive educators, can play a role in overcoming these obstacles. The results of this study show that a philosophical approach that emphasizes active and participatory learning experiences can be a solution in overcoming the challenges of implementing the Independent Curriculum. This article provides insights that can support efforts to design learning strategies that are more effective and in line with holistic educational goals.